A participação popular em conselhos locais de saúde de Camaçari-BA: um olhar a partir do envolvimento dos usuários - Pereira, Francy Webster de Andrade (2011)
The present study deals with the Popular Participation by the involvement of users in the Local Health Councils (CLS) in Camaçari, Bahia. He presented the following objectives: analyses the Brazilian National Health System´s users and popular organizations participation into Local Health Counsels in Camaçari – Bahia, know the creation‟s history of the Local Health Counsels - LHC, analyses the permanent education process of the Health Counsels, identify the major actions and challenges involved in formation of the LHC in Camaçari, reflected about the pedagogic process involved in relationship among social movements, health workers and health directors in creation´s process of local popular participation. It is a quantitative and qualitative study that uses the Epinfo. 6.04 program into treatment of quantitative data and research material analyses to interpretation of the qualitative results. It was done the analysis of information from forty-five (45) counsels with questionnaires and interviewed sixteen persons into four (4) researched territories witch have the LHC. Results are presented from the LHS and Citizen Participation: on the political and pedagogical. Showed that the first experiments date back to 1983 in the suburbs of the city, then strengthened and expanded from 2005, making from the Health Policy of the Municipality. The profile we saw that the majority of the directors representing the communities (users), especially with the presence of women, adults and seniors, with enrollment of high school. Many of those involved with social movements in the neighborhood or the city of Camaçari. In all LHC had elections, especially users, but the vast majority had no training. The main possibilities of these spaces show up as a channel in the construction of power decentralization to community empowerment, and health workers, with effective monitoring of local actions, but an incipient construction of a new citizenship when dialogued with the paternalistic culture while the challenges are highlighted, as offering minimal infrastructure necessary for the functioning of LHS, the organization of a permanent education policies, health councilors, especially articulated with the Municipal Health Council, focusing on training and emphasis of education policy People, strengthen the coordination of local health counselors with local social movements and lastly, joint and strengthen the support of the Camaçari‟s Municipal Secreriat of Health and Municipal Health Counsels of Local Health Counsels, especially in the process of community mobilization and structuring LHS.